1988
DOI: 10.1089/hyb.1988.7.309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Monoclonal Antibodies (MAb 17-1A) in Patients with Metastatic Colorectal Carcinomas

Abstract: Ten patients with metastatic colorectal carcinoma were treated with MAb 17-1A (IgG2A). Before infusion, MAb was incubated in vitro with isolated autologous blood mononuclear cells. Treatment was given in repeated courses (2-4 times) to a maximum dose of 1000 mg of MAb 17-1A. One patient achieved a clinical complete remission, two patients had a minor response and one patient had stable disease for 5 months. The median survival for the four responders was 19 months compared to 7 months for the six non-responder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Several immunotherapeutic trials of human cancer using mAbs showed encouraging results [3,5,6,9,[16][17][18]. The mechanisms involved in such antibody-directed tumor remission remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Several immunotherapeutic trials of human cancer using mAbs showed encouraging results [3,5,6,9,[16][17][18]. The mechanisms involved in such antibody-directed tumor remission remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…This mAb also inhibits the growth of human tumor xenografts in nude mice (3). In patients with colon and pancreatic cancer treated with mAb C017-1A, complete and partial remissions have been described (7,8,(14)(15)(16)(17). However, murine immunoglobulins administered to humans have a short half-life (12-18 hr) and induce an anti-mouse immunoglobulin response (7,8,18).…”
mentioning
confidence: 99%
“…They were chosen since each patient had many consecutive sera avail able and all had well-documented tumor staging. The characteristics of the patients and the treatment schedule have been described earlier [9] and are sum marized in table 1. The patients investigated were also subject to treatment with mouse monoclonal antibodies (Mab) against the tumor-associated anti gen CO 17-1A [9].…”
Section: Patientsmentioning
confidence: 99%